The Impact of Implementation of Government Accounting Standards on the Quality of Government Financial Reports - Rumapea, Ega Priscilla; Napitupulu, Evelin Demiana Lovely; Zahra, Fatimah (Economic: Journal Economic and Business, 2024)
The objectives to be obtained from this research are: 1. To determine the effect of implementing government accounting standards on the quality of financial reports of the regional government of Medan City Regency. 2. Find out whether the Regional Financial Reports of Medan City Regency meet government accounting standards. Type of Research This research is causal associative research according to Sugiyono: research that aims to analyze the causal relationship between independent variables, namely variables that influence and dependent variables, namely variables that are influenced. This means that in this study, researchers want to know and provide empirical evidence about the effect of implementing government accounting standards on the quality of financial reports in accordance with PP number 71 of 2010 at the North Sumatra Province Plantation and Livestock Service. In achieving the objectives that have been set to find out whether the implementation of government accounting standards has an effect on the quality of the financial reports of the North Sumatra Province Plantation and Livestock Service as a benchmark for preparing financial reports and to prevent deviations caused by certain parties. Judging from the determinant coefficient value shown by the Adjusted R square, namely 0.842, it shows that 84.2%, this means that 84.2% of the implementation of government accounting standards has an effect on the quality of the financial reports of the North Sumatra Province Plantation and Livestock Service revenue agency, while it is 15.8 % explained by other factors not examined in this study.